Model Minority Reconstruction in ONE OK ROCK’s “Stand Out Fit In” - Maria Niayu Risma Novianti (General English Education, 2025)
The study explores the model minority myth represented in one of ONE OK ROCK’s songs “Stand Out Fit In” written in English. The concept of model minority attributes the image of Asian American as hard workers in terms of academic and economic achievement in a White society, but it neglects the psychological well-being due to the pressure from Asian American parental expectation and the racism faced by Asian American adolescents. Therefore, the study aims to reconstruct the model minority concept through the analysis of song lyrics and music video scenes of “Stand Out Fit In” by using a discourse analysis framework focusing on the narrative techniques. The result shows that the activity scheme including the repetition of ‘stand out fit in’ in the lyrics and the Bian Lian dance performance in several scenes suggest the new model of model minority proposing the biculturalism concept which is not only maintaining the image of Asian American as high achievers, but also ‘fit[ting] in’ the mainstream society to challenge racism and bias perception of Asian American. This new concept of model minority indicates the cultural adoption strategy, which may lead to Asian Americans' position as ‘honorary white’ in the White supremacy.